2012
DOI: 10.1002/prot.24123
|View full text |Cite
|
Sign up to set email alerts
|

Conformational selection and induced changes along the catalytic cycle of Escherichia coli dihydrofolate reductase

Abstract: Protein function often involves changes between different conformations. Central questions are how these conformational changes are coupled to the binding or catalytic processes during which they occur, and how they affect the catalytic rates of enzymes. An important model system is the enzyme dihydrofolate reductase (DHFR) from Escherichia coli, which exhibits characteristic conformational changes of the active-site loop during the catalytic step and during unbinding of the product. In this article, we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 76 publications
4
41
0
Order By: Relevance
“…It has been noted that in prokaryotes (such as E. coli) the concentrations of NADPH and NADP + are similar, whereas in eukaryotic cells the concentration of NADP + is typically 100 times smaller than the NADPH concentration (33). Therefore, a large K p value in E. coli would significantly stall the DHFR catalytic cycle through a greater degree of product inhibition, where…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been noted that in prokaryotes (such as E. coli) the concentrations of NADPH and NADP + are similar, whereas in eukaryotic cells the concentration of NADP + is typically 100 times smaller than the NADPH concentration (33). Therefore, a large K p value in E. coli would significantly stall the DHFR catalytic cycle through a greater degree of product inhibition, where…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the binding of inhibitors, such as TMP to ecDHFR, can affect the conformational states of the protein (34). Because the flexible PEKN domain resides over the TMP binding pocket [Protein Data Bank (PDB) ID2W3A] (15), the local conformational fluctuations in this region should affect the binding and dissociation of ligands (17,33,35). Again, within experimental errors, all PEKNcontaining ecDHFR variants show the same binding affinity for TMP, and neither the L28F nor the N23PP mutations exhibit any additional impacts on TMP binding.…”
Section: Resultsmentioning
confidence: 99%
“…The loop interactions in DHFR are also likely important for catalytic flux, which may depend on the cellular environment and NADP + /NADPH concentrations . For example, the occluded conformation is disfavored by a polyproline sequence at the C‐terminal end of the Met20 loop in human DHFR.…”
Section: Modulation Of Loop Dynamicsmentioning
confidence: 99%
“…The temporal ordering of the conformational changes and binding events of the pathway requires transition times for ligand binding and unbinding that are small compared to the dwell times in the states P 2 and P 2 L (see text). The effective on‐ and off‐rate constants of the pathway are konu12k2+b23/(u21k2+u21b23+k2+[L]b23) and koffu21k2b32/(u21k2+u21b23+k2+[L]b23) …”
Section: Conformational Selection and Induced Changes Are Two Sides Omentioning
confidence: 99%
“…Under “pseudo‐first order” conditions with a ligand concentration [L] that greatly exceeds the protein concentration, the relaxation process of the two‐step binding mechanisms in Figure (a,b) is a bi‐exponential process . The slower, dominant rate of this process has the general from kobs=k1=12true(σσ24ρtrue) while the faster rate is k2=12true(σ+σ24ρtrue).…”
Section: Effective Overall Rates Of Conformational‐selection and Indmentioning
confidence: 99%